A semi-supervised feature selection method using a non-parametric technique with pairwise instance constraints. (June 2013) - Chen, Chien-Hsing
Many feature selection methods based on supervised learning have investigated side information that considers labelled instances. In this paper, we present a new feature selection method for semi-supervised learning, helped by side information, and the selected features are useful for discovering natural clusters. To select salient features for clustering, most existing wrapper-based feature selection methods study features from the partitioned clusters that result from a prespecified clustering algorithm. The selected features often suffer from both noisy features participating in the partitioning process and bias in the clustering algorithm selection. To overcome these problems, our method does not need clustered information to train features. In particular, our method uses side information to select features directly from the nearest and the farthest neighbours regardless of any clustering algorithm helping to partition data into clusters; specifically, the side information is considered to form pairwise instance constraints to guide the feature selection process and assign a weight for each instance for training. Experimental results indicate that our method, tested on image datasets, outperforms many well known wrapper-based feature selection methods in selecting features for clustering.